(untitled) - World Bank Technology Paper (Washington D.C, 1998)
Over 245 river basins are shared by two or more states. About forty percent of the world population and 50 percent of its land are either dependent on or stand to benefit from the waters available in these basins.
Keywords: International lakes,International rivers,Water resources development; International cooperation